PvGAMA reticulocyte binding activity: predicting conserved functional regions by natural selection analysis (2017)
Background: Adhesin proteins are used by Plasmodium parasites to bind and invade target cells. Hence, characterising molecules that participate in reticulocyte interaction is key to understanding the molecular basis of Plasmodium vivax invasion. This study focused on predicting functionally restricted regions of the P. vivax GPI-anchored micronemal antigen (PvGAMA) and characterising their reticulocyte binding activity. Results: The pvgama gene was initially found in P. vivax VCG-I strain schizonts. According to the genetic diversity analysis, PvGAMA displayed a size polymorphism very common for antigenic P. vivax proteins. Two regions along the antigen sequence were highly conserved among species, having a negative natural selection signal. Interestingly, these regions revealed a functional role regarding preferential target cell adhesion. Conclusions: To our knowledge, this study describes PvGAMA reticulocyte binding properties for the first time. Conserved functional regions were predicted according to natural selection analysis and their binding ability was confirmed. These findings support the notion that PvGAMA may have an important role in P. vivax merozoite adhesion to its target cells. © 2017 The Author(s).